2005
DOI: 10.1186/1471-2202-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Iron is necessary for neuronal function but in excess generates neurodegeneration. Although most of the components of the iron homeostasis machinery have been described in neurons, little is known about the particulars of their iron homeostasis. In this work we characterized the response of SH-SY5Y neuroblastoma cells and hippocampal neurons to a model of progressive iron accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Coimmunoprecipitation of Fpn with different epitope tags, as well as the detection of a complex much larger than the monomer by size-exclusion chromatography, indicated that the functional unit of Fpn is a multimer. This result is consistent with the observation by Aguirre et al (21), who suggested that Fpn was dimeric. Coimmunoprecipitation showed that Fpn mutants could also form multimeric complexes with WT Fpn.…”
Section: Discussionsupporting
confidence: 83%
“…Coimmunoprecipitation of Fpn with different epitope tags, as well as the detection of a complex much larger than the monomer by size-exclusion chromatography, indicated that the functional unit of Fpn is a multimer. This result is consistent with the observation by Aguirre et al (21), who suggested that Fpn was dimeric. Coimmunoprecipitation showed that Fpn mutants could also form multimeric complexes with WT Fpn.…”
Section: Discussionsupporting
confidence: 83%
“…12,25,26 As in the periphery, Fpn1 is the sole known cellular iron exporter and plays a key role in brain iron release. 22,46 The turnover of Fpn1 is controlled by hepcidin. Injection of hepcidin into the lateral cerebral ventricle resulted in decreased Fpn1 protein content in the cerebral cortex, the hippocampus, and the striatum.…”
Section: Figmentioning
confidence: 99%
“…Mammalian cellular iron efflux is mediated by the sole iron exporter ferroportin 1 (Fpn1), a transmembrane protein. 22 The abundance of Fpn1 on the plasma membrane can be modulated by interaction with its ligand hepcidin, an iron regulatory hormone produced in the liver in response to inflammatory stimuli, iron, and hypoxia. 23 Hepcidin binds to Fpn1 and induces its internalization and degradation, resulting in decreased cellular iron export and subsequent iron acuumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Western Blot Analysis-Cells extracts were prepared as described (30). Proteins were resolved in 10% Laemmli SDSpolyacrylamide gels, transferred to polyvinylidene fluoride membranes (Millipore Corp.), and incubated overnight with primary antibody.…”
Section: Methodsmentioning
confidence: 99%